Effect of PH and Powder to Liquid Ratio on the Solubility of a Conventional Glass Ionomer Luting Cement - Ali Hamad Khan, Amjad Hanif, Shahid Ilyas, Sarah Hussain Khattak, Abdul Hanan, Sajid Hussain, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Properties of GI luting cements are influenced by complex oral environment. This in-vitro study is designed to simulate oral conditions for better understanding behavior of GI luting cement in oral cavity and to evaluate its solubility. Fluctuating oral environment from acidic to alkaline is thought to cause solubility of luting agent, which insults the integrity of luting agents leading to micro leakage and ultimately luting failure of restorations. An attempt via this study was made to funnel powder liquid ratio for dental practice by exposing different P/L ratio to varying pHs of artificial saliva solution. Materials and Methods: Four groups of specimens were prepared using different powder liquid ratios (Group A 1:2, group B 1:3, group C 1.5:3 and group D 2:3S). Specimens were desiccated for 2 hours in hot air oven and weighted with digital analytical balance. Specimens were immersed in respective artificial saliva for a week, desiccated for 2 hours, weighed and solubility was calculated. Micrographs of specimens were taken with scanning electron microscope. Descriptive statistics such as mean, range and standard deviation values were presented as tables and charts. variation of means amongst groups were analysed using One-way analysis of variance (ANOVA). P value of ≤ 0.05 was considered significant Results: Solubility of specimens immersed in acidic artificial saliva solution showed elevated solubility. One-way ANOVA showed statistically significant results, Tukey’s HSD showed that specimen of group A2 showed elevated solubility of 0.000246790 mg/mm3 and specimens of group D1 showed less solubility of 0.000003466mg/mm3. Conclusion: Unlike manufacturer recommended P/L ratio, this study concluded that P/L ratio of 2:3 is a better GI luting cement as it exhibited least solubility in both acidic and basic environments. Keywords: Luting, GI luting cement, solubility, salivary pH